ANALISIS KEMAMPUAN NUMERASI SISWA KELAS VIII SMP SE-KOTA SUNGAI PENUH DALAM MENYELESAIKAN SOAL AKM - Sonya Fiskha Dwi Patri; Sonya Heswari (Jurnal Muara Pendidikan, 2022)
The national assessment is a government policy based on Permendikbudristek number 17 of 2021 which has been implemented in schools including junior high schools in Sungai Penuh City. National assessments are still common among teachers, students and other stakeholders, but with the existence of a national assessment program policy as a substitute for the National Examination, schools are not ready to be required to carry out a national assessment, one of which is the Minimum Competency Assessment (AKM). Data on the readiness for AKM implementation needs to be known, especially students' numeracy skills in solving AKM questions to obtain clear data-based corrective steps. This research is a descriptive study that aims to describe the preparation and numeracy skills of junior high school students in Sungai Penuh City in solving AKM questions. The study used 2 instruments, namely the AKM numeracy question and a student perception questionnaire. From the analysis results obtained data on the ability to solve numerical AKM questions with an average student score of 57.36 and an average number of criteria scores of 2.80 in the medium category. The data shows that the numeracy skills of junior high school students in Sungai Penuh need to be improved and there is a need for an introduction to literacy and numeracy questions since students sit in class VII so that when implementing AKM in class VIII students are accustomed to solving literacy and numeracy questions with various types of questions.